Information Technology: A Study of its Concept and Importance in Educational Institutions - Al-Taai, Suaad Hadi Hassan (Webology, 2022)
The study of the subject of information technology is very important, especially at the present time, and in all fields, especially educational institutions, because of its great impact on its progress and its economic, scientific and social superiority. The research addressed the topic of the concept of information technology and its objectives, and the most important reasons for its use, investment capabilities and importance. The research indicated the most important advantages and functions of information technology, and its optimal strategic use. As well as discussing the topic of information technology infrastructure and capacity building. The research discussed the components of information technology in most fields, especially in educational institutions, and its most prominent characteristics. The research sheds light on the benefits of using information technology in education, the most important obstacles, and the most prominent advantages of using information technology for a university professor. The research addressed the issue of the most important obstacles to the use of information technology in education and the negative effects resulting from the excessive use of information technology.